2020
DOI: 10.1002/alz.12231
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of brain atrophy subtypes categorization in memory clinics

Abstract: Introduction The clinical relevance of brain atrophy subtypes categorization in non‐demented persons without a priori knowledge regarding their amyloid status or clinical presentation is unknown. Methods A total of 2083 outpatients with either subjective cognitive complaint or mild cognitive impairment at study entry were followed during 4 years (MEMENTO cohort). Atrophy subtypes were defined using baseline magnetic resonance imaging (MRI) and previously described algorithms. Results Typical/diffuse atrophy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 43 publications
0
19
1
Order By: Relevance
“…We did not find any differences in the progression rate between the hippocampal subtypes. Previous studies have found conflicting results concerning the progression rate in atrophy subtypes [3, 6-8, 11, 12]. As we do not know the cortical atrophy component in the patients in the present study and cortical atrophy has been found to be the driver of progression rate, conclusions are hard to make based on our data [11].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…We did not find any differences in the progression rate between the hippocampal subtypes. Previous studies have found conflicting results concerning the progression rate in atrophy subtypes [3, 6-8, 11, 12]. As we do not know the cortical atrophy component in the patients in the present study and cortical atrophy has been found to be the driver of progression rate, conclusions are hard to make based on our data [11].…”
Section: Discussioncontrasting
confidence: 81%
“…Findings on the clinical progression rate of the various subtypes have been inconsistent. Some studies reported a faster progression in typical and hippocampal sparing AD [3, 6, 11], and others have found faster progression in typical and limbic predominant types [7, 12], while our group did not find any difference in the progression rate in a previous study [8]. The focus on AD subtypes is important as differences in clinical symptomatology, progression rate, regional vulnerability, and possibly underlying neurobiology could have a major impact on both clinical workup and follow-up and in treatment trials [13].…”
Section: Introductionmentioning
confidence: 99%
“…From the conceptual point of view, it is essential to keep in mind that the present MRI staging scheme (such as the Braak staging scheme) only describes the most frequent ‘limbic-predominant’ and ‘typical’ progressions of Alzheimer’s disease. 36 , 37 This model only describes the ‘average’ structural course of Alzheimer’s disease and does not apply to ‘atypical’ Alzheimer’s disease, such as logopenic primary progressive aphasia, posterior cortical atrophy or behavioural Alzheimer’s disease, which are driven by different patterns of atrophy and represent less common ‘extremes’ of the Alzheimer’s disease anatomical spectrum. 38 Indeed, the methodology used in the present work does not take into account the recent description by Vogel et al 39 of distinct trajectories of tau deposition in Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies demonstrated the limbic-predominant atrophy pattern of AD [ 43 45 ]: the thickness of the isthmus cingulate was reported to decrease in AD patients and it was also shown to be associated with the cognitive level [ 46 , 47 ]. Our results further support the role of the isthmus cingulate in the progression of AD.…”
Section: Discussionmentioning
confidence: 99%